Neurovascular Coupling by Functional Near Infra-Red Spectroscopy and Sport-Related Concussion in Retired Rugby Players: The UK Rugby Health Project - Sharma, Anick; Hind, Karen; Hume, Patria; Singh, Jyotpal; Neary, J. Patrick (Frontiers in Human Neuroscience, 2020)
Aim: This study investigated cerebral hemodynamic responses to a neurovascular coupling (NVC) test in retired contact athletes with a history of repeated mild traumatic brain injury (mTBI) and in controls with no history of mTBI. Methods: Twenty-one retired rugby players (47.7 ± 12.9 year old; age at retirement: 38.5 ± 8.9 year; number of years playing rugby: 12.7 ± 3.7 year) with a history of three or more diagnosed concussions (8.9 ± 7.9 concussions per player) and 23 controls with no history of mTBI (46.5 ± 12.8 year old) performed a NVC test to detect task-orientated cerebral hemodynamic changes using functional near-infrared spectroscopy (fNIRS). Results: The NVC showed a statistically significant reduction in the cerebral hemodynamic response in comparison to the control group which had a greater relative increase of oxyhemoglobin (O2Hb). There were reductions in left middle frontal gyrus (MFG) O2Hb (−0.015 ± 0.258 μM) and relative increases in deoxyhemoglobin (HHb; −0.004 ± 0.159 μM) in the same region for the mTBI group in comparison to the control group (−0.160 ± 0.311 μM; −0.121 ± 0.076 μM for O2Hb and HHb, respectively). The mTBI group induced a greater rate of oxygen extraction compared to the control group. Conclusion: This was the first study to examine cerebral hemodynamic changes in retired rugby players in response to a NVC test, and we found reduced cerebral hemodynamic responses in participants with a history of mTBI compared to controls. These results suggest altered cerebral metabolic demands in participants with a history of multiple head injuries. Further research is needed to ascertain an understanding of the changes in hemodynamics from playing into retirement.